Investigation on Fish Assemblages around Cooling Water System Outlet in the Coastal Water of Bontang City, East Kalimantan (Global Journal of Science Frontier Research, 2013)
The community structure and assemblage of fish caught in the water around cooling water system outlet of a methanol industry in Bontang City were investigated. Sampling of fish was done in spring tide at high water level (HWL) and low water level (LWL) and neap tide in January to February 2013. Fishing gears used for sampling were bottom minitrawler and angler. Surface water temperature and salinity were measured using water checker Horiba U-50 series. Tide and water depth including water current were also surveyed using tidal scale pole, echosounder GPSmap 2108 Garmin and Braystoke BFM001 current meter respectively. The assemblage of fish caught in water around the outlet composed of 57 different species with 5670 individuals. The most common fish species observed around the outlet and in water intake was from the member of family Leiognathidae and Lutjanidae. Certain species of Nemipteridae seemed to withstand temperature pressure. Fish assemblage was greatly influenced by tidal cycle. The water condition around outlet was included as relatively good indicated by the number and species of fish caught.
Keywords: cooling water system outlet; tide; water temperature; salinity; bontang city